ChemInform Abstract: Evidence of a Mixed Magnetic Phase in EuMgGe: A Semimetallic Zintl Compound with TiNiSi Structure Type. Issue 43 (21st October 2014) - Slabon, Adam; Cuervo‐Reyes, Eduardo; Niehaus, Oliver; Winter, Florian; Mensing, Christian; Poettgen, Rainer; Nesper, Reinhard
Abstract EuMgGe is prepared by melting and annealing the elements (Nb tube, 1.